Hubungan antara Tumor-Infiltrating Lymphocytes dengan Stadium dan Derajat Diferensiasi Adenokarsinoma Kolorektal - Karina E. Clearesta; Toar Mambu; Ferdinand Tjandra; Fredrik G. Langi (Universitas Sam Ratulangi, 2024)
Abstract: Colorectal cancer has high incidence and mortality rates. Tumor-infiltrating lymphocytes (TILs) are histopathological findings that depict the individual's immune response to the tumor. This study aimed to investigate the relationship between TILs and the differentiation grade and stage of colorectal adenocarcinoma. This was an analytical and observational study with a cross-sectional design. The results showed 34 patients with colorectal adenocarcinoma who met the criteria. The sample characteristics consisted of male (64.7%), mean age (59.15 ± 10.78), tumor location in the colon (43.9%) and rectum (55.8%), average TILs (25.62 ± 17.39), moderate TILs grade (50%), stage III tumor (50%), and moderately differentiated tumors (70.6%). A significant association was found between TILs and tumor differentiation grade (p=0.024). Post hoc analysis showed a significant difference in TILs between good and poor differentiation (p=0.04; 95% CI: 1.52-64.48). A cut-off value for TILs was identified for good differentiation (TIL>27) and moderate/poor differentiation (TIL≤27) with a sensitivity of 69.2% and specificity of 75.0%. The extent of lymphocytic invasion of tumor tissue reflected the host's immune status. TILs played an important role in tumor development and was a good prognostic factor in colorectal cancer. In conclusion, TILs can be used as a predictor for the differentiation grade of colorectal adenocarcinoma. Keywords: colorectal adenocarcinoma; tumor infiltrating lymphocytes; differentiation grade Abstrak: Kanker kolorektal memiliki angka kejadian dan mortalitas tinggi. Tumor-infiltrating lymphocytes (TILs) merupakan temuan histopatologik yang menggambarkan respon imunologis individu terhadap tumor. Penelitian ini bertujuan untuk mengetahui hubungan antara TILs dengan derajat diferensiasi dan stadium pada adenokarsinoma kolorektal. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Hasil penelitian mendapatkan 34 pasien dengan adenokarsinoma kolorektal yang memenuhi kriteria. Karakteristik sampel terbanyak ialah jenis kelamin laki-laki (64,7%), rerata usia (59,15 ± 10,78), lokasi tumor di kolon (43,9%) dan rektum (55,8%), rerata TILs (25,62 ± 17,39), derajat TILs moderate (50%), stadium tumor derajat III (50%) dan derajat diferensiasi tumor sedang (70,6%). Terdapat hubungan bermakna TILs dengan derajat diferensiasi tumor (p=0,024). Analisis post hoc bermakna terhadap derajat TILs baik vs buruk (p=0,04; 95% CI: 1.52-64.48). Nilai cut-off TILs dengan derajat diferensiasi baik (TIL>27) dan sedang/buruk (TIL≤27) dengan sensitivitas 69,2% dan spesifisitas 75,0%. Luasnya invasi limfositik pada jaringan tumor mencerminkan status kekebalan tubuh pejamu. TILs berperan penting dalam perkembangan tumor dan merupakan faktor prognostik yang baik pada kanker kolorektal. Simpulan penelitian ini ialah nilai TILs dapat digunakan sebagai faktor prediktor derajat diferensiasi adenokarsinoma kolorektal. Kata kunci: adenokarsinoma kolorektal; tumor infliltrating lymphocytes; derajat diferensiasi